Implementation of the 'Healthier Drinks at Healthcare Facilities' strategy at a major tertiary children's hospital in Brisbane, Australia - Jacqueline L. Walker; Robyn Littlewood; Ayala Rogany; Sandra Capra (Elsevier, 2020)
Abstract Objective: The World Health Organization recommends people reduce their free sugar consumption to <10% of daily energy intake. This study aimed to determine the viability of the 'Healthier Drinks at Healthcare Facilities' strategy to reduce the amount of free sugar available in beverages and influence consumer purchasing patterns. Methods: Beverage environment modifications at a children's hospital limited the availability of less healthy options. Using a convergent parallel mixed‐methods design, sales data from retail food outlets (n=7) and vending machines (n=14) were collected from January 2017 to May 2018. Employees (n=105) and visitors (n=102) completed surveys, and retail food outlet managers (n=3) completed semi‐structured interviews. Data were analysed via descriptive statistics, independent t‐tests and content analysis. Results: The strategy decreased the availability of less healthy beverages and resulted in a significant increase in the proportion of 'green' (healthier) beverages sold (3%, p=0.002), and a decrease in the proportion of 'red' (less healthy) beverages sold (5%, p=0.011). Overall, sales did not change (p=0.243). The majority of participants supported the strategy. Conclusions: Overall, a shift in consumer purchasing patterns resulted. Further modification of the beverage environment is encouraged to increase impact. Implications for public health: This strategy was feasible and acceptable in a healthcare setting.